2007
DOI: 10.1016/j.jphotochem.2007.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio study of exciton transfer dynamics from a core–shell semiconductor quantum dot to a porphyrin-sensitizer

Abstract: The observed resonance energy transfer in nanoassemblies of CdSe/ZnS quantum dots and pyridyl-substituted free-base porphyrin molecules [Zenkevich et al., J. Phys. Chem. B 109 (2005) 8679] is studied computationally by ab initio electronic structure and quantum dynamics approaches. The system harvests light in a broad energy range and can transfer the excitation from the dot through the porphyrin to oxygen, generating singlet oxygen for medical applications. The geometric structure, electronic energies, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 86 publications
2
80
0
Order By: Relevance
“…In this case, like for multiporphyrin complexes (described above), a controllable formation of "QD-Porphyrin" nanoassemblies have been realized as a surface passivation of CdSe/ZnS ODs by tetrameso-pyridyl substituted porphyrins (free base and/or Cu-complex) in titration experiments. [29,[90][91][92][93][94][95][96][97][98][99] It is well-known from chemical background that the 3d transition metal Zn 2+ ion (of ZnS shell) has empty 3d 10 orbital while heteroatom N-pyr of the porphyrin mesopyridyl ring is a very good e-donor having an unshared electron pair. Thus, in this case a "key-lock" principle is realized via oneor two-fold non-covalent coordination Zn….N-pyr.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, like for multiporphyrin complexes (described above), a controllable formation of "QD-Porphyrin" nanoassemblies have been realized as a surface passivation of CdSe/ZnS ODs by tetrameso-pyridyl substituted porphyrins (free base and/or Cu-complex) in titration experiments. [29,[90][91][92][93][94][95][96][97][98][99] It is well-known from chemical background that the 3d transition metal Zn 2+ ion (of ZnS shell) has empty 3d 10 orbital while heteroatom N-pyr of the porphyrin mesopyridyl ring is a very good e-donor having an unshared electron pair. Thus, in this case a "key-lock" principle is realized via oneor two-fold non-covalent coordination Zn….N-pyr.…”
Section: Methodsmentioning
confidence: 99%
“…[29,[90][91][92][93][94][95][96][97][98][99]123] Structures of QDs and porphyrin molecules as well as necessary details explaining the formation of nanoassemblies "QD-Porphyrin" are shown in Figure 9. The results described below concern to the analysis of the interaction between semiconductor CdSe/ZnS quantum dots and surface attached porphyrin molecules (free base and Cu-complex) in order to evaluate the influence of tetrapyrrolic macrocycle on pathways and mechanisms of exciton relaxation in "QD -Cu-porphyrin" nanoassemblies.…”
Section: Tuning Electronic States Of Cdse/zns Quantum Dot By One Cu-pmentioning
confidence: 99%
“…Here, we focus presumably on nanocomposites based on TOPO-capped CdSe/ZnS QDs and H 2 P(m-Pyr) 4 molecules (or H 2 P, Figure 1A) showing among a series of pyridyl substituted free-base porphyrins the most effective PL quenching of QDs at the same titration conditions ( Figure 4B). Due to the simultaneous observation of FRET and non-FRET PL quenching processes for QDs in "QD-Porphyrin" nanocomposites, [46][47][48][49][50]53] which serves as an indicator for the nanocomposite formation we have the direct access to QD surface-related processes. The detailed analysis of a whole series of titration experiments to study the PL intensity of CdSe/ZnS QDs as a function of the added amount of H 2 P(mPyr) 4 molecules within time scale from 60 s to minutes and hours as well as of solvent (toluene or n-octane) has been presented in our recent paper.…”
Section: Manifestation Of Temporal Porphyrin and Capping Ligand Exchamentioning
confidence: 99%
“…[31][32][33][34][35][36][37][38] Inspired by our earlier work on self-assembled multiporphyrin arrays [39][40][41][42][43][44][45] we have elaborated the experimental approach in the direct labelling of trioctylphosphine oxide (TOPO)-and amino (AM) -capped semiconductor quantum dots (QD) CdSe/ZnS with functional ligands (dyes) of two types (pyridyl substituted porphyrins and heterocyclic pyridyl functionalized perylene diimide molecules) in liquid solutions and polymeric matrixes. [46][47][48][49][50][51][52][53][54][55] We have shown that depending on redox and electronic properties of interacting subunits as well as anchoring groups (connecting organic and inorganic counterparts) the formation of "QD-Dye" nanocomposites allows for a controlled realization of mutually relative (spatial) orientations and electronic energy scales in order to optimize intended photoinduced processes such as charge transfer, [56,57] fluorescence Foerster energy transfer (FRET) [20,46,47,50,52] or electron tunnelling in the conditions of quantum confinement (non-FRET process). [48,50,53] Typically, all these processes lead to the pronounced quenching of QD photoluminescence (PL) in nanocomposites that may be used as an indicator of complex interface phenomena selectively depending on attached ligands (porphyrins, perylene diimides, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The structural formulas of 5,10,15,20-tetra-metapyridylporphyrin P (a) and trioctylphosphine oxide TOPO (b) and a diagram of the CdSe/ZnS nanocrystals-porphyrin ligand composite (c): r m = 7.55 Å, radius of the optimized structure of the porphyrin molecule (HyperChem, release 4.0, semiempirical PM3 method [35]); in the diagram (c) the dimensions of the CdSe core, the number of ZnS monolayers, and the porphyrin and TOPO molecules are represented in the actual relative scale. According to experimental data on quenching of the photoluminescence of the nanocrystals by porphyrins with various numbers of mesopyridyl anchor groups [15] and molecular modeling of the structure of the nanocomposites [35], two-point interaction secures a predominantly perpendicular arrangement of the plane of the porphyrin macrocycle and the surface of the NC. the employed components and the small optical densities of the investigated solutions.…”
mentioning
confidence: 99%